Relationship Between Career Adaptability and Job Crafting - Mariana de Almeida Klotz Teixeira; Milena Miyuki Hiratuca Ujihara; Rita Pimenta de Devotto; Clarissa Pinto Pizarro de Freitas; Jaqueline de Carvalho Rodrigues (Paidéia (Ribeirão Preto))
Abstract Working conditions have undergone major changes that have created a different dynamic with respect to the career trajectories of individuals. The objective of this study was to analyze how personal characteristics (the four dimensions of career adaptability) explain job crafting (proactive actions on the part of the individual) and whether there is a specific aspect with greater impact in this relationship. Two hundred and ninety-nine employees participated by completing a socio-demographic questionnaire, the Career Adaptability Scale, and the Job Crafting Scale. Network analysis and regression revealed a strong relationship between worry, control, curiosity, trust, relational crafting, task crafting, and cognitive crafting. Although all relationships were positive, curiosity stood out as the factor that most influenced work crafting. The study contributes to the understanding of the intimate relationships between career adaptability and the three forms of job crafting.